ANALISIS PRAKTIK KERJA SAMA PENGELOLAAN LAHAN PERTANIAN MAHAD AL-ZAYTUN OLEH P3KPI PERSFEKTIF MAZHAB HANAFI - Ramdan, Muhamad; Prawoto, Imam; Asrof Fitri, Ahmad (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Indonesia as an agricultural country faces the challenge of many landless farmers. Akad muzaraah is a relevant solution, especially for Muslim communities. According to the Hanafi school, particularly Abu Yusuf and Muhammad Ash-Shibani, this contract is valid if the landowner provides capital and agricultural needs, while the farmer manages the land. This system helps farmers without land or capital according to sharia principles. The purpose of this study is to analyze the practice of Mahad Al-Zaytun agricultural land management cooperation by the Indonesian food security support farmers association and to analyze the practice of Mahad Al-Zaytun agricultural land management cooperation by the Indonesian food security support farmers association according to the Hanafi Mazhab. The method used is field research with a qualitative approach. Data was collected through observation, interviews, and documentation. The results of this study concluded that: 1. In practice, the land management cooperation between Mahad Al-Zaytun and P3KPI applies a profit-sharing system. In this cooperation, Mahad Al-Zaytun provides land and capital for agricultural needs, while P3KPI is responsible for cultivation. Profit sharing is carried out with a proportion of 50% for each party, after deducting capital. Risk management in this cooperation is carried out proportionally, where losses due to natural disasters are borne together, while negligence is the responsibility of the guilty party. 2. This cooperation is regulated in an MoU that contains an agreement. The land used is productive land, with quality seeds. This muzaraah agreement ends after the harvest is completed in accordance with the planting cycle. In risk sharing, where failures due to natural disasters are borne together, while negligence is the responsibility of the parties concerned. With this, the cooperation between Mahad Al-Zaytun and P3KPI in agricultural land management reflects the concept of muzaraah, its pillars and conditions in accordance with the Hanafi Mazhab according to Abu Yusuf and Muhammad Ash-Shibani. Keywords: Agricultural Land, Hanafi Mazhab, Cooperation.